Prevalence of anti-hypertensive drug prescription in Thailand, a cross sectional study using National Health Security Office database - Theerut Luangmonkong; Jiratchaya Wongsaardsakul; Rujipas Laobutree; Sarawut Jindarat; Nattapon Jaisupa (Faculty of Pharmacy, Mahidol University, 2022)
Individual conditions are essential in pharmacotherapy of hypertension; however, information regarding the association between anti-hypertensive drugs and co-morbid diseases as recommended in clinical practice guidelines is not well acquainted. Therefore, this study aimed to report the prevalence of prescribed anti-hypertensive drugs using Thailand National Health Security Office database. In 2014, we found that calcium channel blockers (CCBs), angiotensin converting enzyme inhibitors (ACEIs), and diuretics, were prescribed in 56.11%, 42.70%, and 33.58% of total patients, respectively. Similarly in 2015, CCBs and ACEIs were prescribed in 57.69% and 41.01% of total patients, whereas the 3rd most frequently prescribed was anti-adrenergics (28.55%). As recommended in the latest Thailand clinical practice guideline at that period, as a mono-therapy, patients younger than 55 years old without co-morbid diseases received either ACEIs (28.91% and 28.40%) or ARBs (6.70% and 6.33%); however, CCBs were prescribed to these patients in the highest percentage (33.25% and 40.35% in 2014 and 2015, respectively). Focusing on patients with co-morbid conditions, CCBs were prescribed at 54.23% and 55.72% in patients with diabetes mellitus and 62.53% and 62.58% in patients with chronic kidney diseases in 2014 and 2015, respectively. The percentages of patients with chronic kidney diseases who received CCBs were relatively higher than those treated with either ACEIs or ARBs, the first-line recommendation. Interestingly, we found the inappropriate combination between ACEIs and ARBs. Our finding revealed that although the anti-hypertensive drug prescription in Thailand was in line with the recommendations in clinical practice guidelines, certain problematic prescriptions remained available.